Ethnic Identity through Character Construction: Examining Semantic Essence of Yoruba Names in Femi Adebayo’s Jagun Jagun and Bode Sowande’s Arede Owo - Kareeem Kolawole Ganiyu; Babatunde Covenant Olugbenga; Emmanuel Godwin Kalu (LingLit Journal Scientific Journal for Linguistics and Literature, 2025)
This study looks into the significance of thematic nomenclature in character construction within the rich cultural lineage of the Yoruba tradition, as depicted in the film "Jagunjagun" by Femi Adebayo and the stage play "Arede owo” by Bode Sowande. Through meticulous linguistic analysis of character names, this research uncovers the layers of meaning interwoven into each name, serving as a reflection of socio-cultural themes and enhancing narrative complexity. In "Jagunjagun", names such as Gbogunmi and Ogundiji resonate with the spirit of war, while in "Arede owo", characters like Ajeigbe and Surulere encapsulate themes of wealth, friendship, and misery. The comic relevance in Arede Owo begins from the choice of names given to character and the theme of war reflect in almost every characters names in the movie Jagun Jagun. Having experienced both the stage play and the film, our methodology involved immersing ourselves in the linguistic mosaic of these works, allowing us to discern the transformative power of language in shaping narrative identity and imbuing characters with authenticity and resonance. It is evident that in Yoruba culture, as in many other cultures, names are imbued with profound meaning, often serving as signifiers of individual identity and societal values. The observation that plays and films with meaningful character names tend to captivate audiences and draw crowds to cinemas and theatres reveals the enduring fascination with the exploration of linguistic symbolism in storytelling. Indeed, the resonance of these works lies not only in their narrative arcs but also in the symbolic weight carried by the characters' names. As such, this study sheds light on the interplay between language, culture, and storytelling.